Preparation of Magnetic Nanoparticles via a Chemically Induced Transition: Presence/Absence of Magnetic Transition on the Treatment Solution Used. (26th January 2016) - Chen, Yanshuang; Chen, Qin; Mao, Hong; Lin, Yueqiang; Li, Jian
Abstract : The dependence of magnetic transition on the treatment solution used in the preparation of magnetic nanoparticles was investigated using as-prepared products from paramagnetic FeOOH/Mg(OH)2 via a chemically induced transition. Treatment using FeCl3 and CuCl solutions led to a product that showed no magnetic transition, whereas the product after treatment with FeSO4 or FeCl2 solutions showed ferromagnetism. Experiments revealed that the magnetism was caused by the ferrimagnetic γ -Fe2 O3 phase in the nanoparticles, which had a coating of ferric compound. This observation suggests that Fe 2+ in the treatment solution underwent oxidation to Fe 3+, thereby inducing the magnetic transition. The magnetic nanoparticles prepared via treatment with an FeSO4 solution contained a larger amount of the nonmagnetic phase. This resulted in weaker magnetization even though these nanoparticles were larger than those prepared by treatment with an FeCl2 solution. The magnetic transition of the precursor (FeOOH/Mg(OH)2 ) was dependent upon treatment solutions and was essentially induced by the oxidation of Fe 2+ and simultaneous dehydration of FeOOH phase. The transition was independent of the acid radical ions in the treatment solution, but the coating on the magnetic crystallites varied with changes in the acid radical ion.